A Protecting Curse - Németh, György (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
The maskelli maskello spell was mostly used to increase the effectiveness of curses on curse tablets and in recipes of magic papyri. Curiously, the incantation appears in the texts of three amulets, one of them on a magic gem preserved in Leiden.